Human papillomavirus infection in esophageal squamous cell carcinoma and esophageal adenocarcinoma: a concise review. Issue 1 (25th October 2020) - Rajendra, Shanmugarajah; Pavey, Darren; McKay, Owen; Merrett, Neil; Gautam, Shweta Dutta
Abstract: The causal link between high‐risk human papillomavirus (hr‐HPV) infection and cervical, anogenital, and some oropharyngeal malignancies has been established by both molecular and epidemiological data. The association between HPV and esophageal squamous cell carcinoma (ESCC) remains controversial, as is the true prevalence of HPV infection in ESCC. The wide range in reported rates reflects variability in the primary literature, with some larger scale case–control studies suggesting the infection rates range from 0% to 78%. Interactions between HPV and the Barrett's metaplasia–dysplasia–carcinoma sequence have been explored, and these studies have shown some conflicting data. Overall, systematic reviews have reported the prevalence of HPV‐positive DNA in esophageal adenocarcinoma patients of between 13% and 35%. Postulated reasons for discrepancies in HPV prevalence rates in esophageal cancer include variations in testing methodology and assay sensitivities; technical issues, including the lack of a gold‐standard primer; types of specimens utilized (fresh‐frozen versus formalin‐fixed tissue); geographical variation; cross‐contamination; and small sample sizes. Thus, efforts must be undertaken to (1) standardize HPV testing, ideally in a central laboratory and utilizing tests that detect viral transcriptional activity; (2) avoid cross‐contamination; and (3) recruit large numbers of patients to accurately ascertain HPV rates in esophageal malignancy.